ETIKA PELAYANAN KONSELING PASTORAL PENDETA BAGI JEMAAT - Nendissa, Julio Eleazer (PT. Giat Konseling Nusantara, 2024)
It is important for a Pastor in his ministry as a servant of God to know his duties and calling. In thiscase, not only as a preacher but also as a counselor who builds relationships with the congregation. Asa counselor, the Pastor must practice pastoral counseling services and first understand ethical issues.The aim of this research is to describe and analyze the ethics of the Pastor's pastoral counselingservices for congregations experiencing problems in their lives. In this paper, the author uses aqualitative research method with a descriptive approach and data collection techniques using literaturein the form of journals, books, articles related to this research so that he can collect data accuratelyand precisely. Based on a review of the literature, the author finds that the ethics of pastoralcounseling services are humanitarian in nature, the role of pastoral counseling in the lives ofcongregations experiencing problems, and a Pastor must have pastoral counseling ethics in whichthere are 4 principles, namely confidentiality, responsibility, awareness of limitations as a Counselor,and knowing basic needs of the congregation. Therefore, various ethics of the Pastor's pastoralcounseling services must be practiced with the congregation so that they can feel the warmth, careand togetherness of a Pastor.